2012
DOI: 10.2176/nmc.52.878
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Endovascular Embolization for Hemangioblastoma in the Posterior Fossa

Abstract: Intracranial hemangioblastomas (HBs) are hypervascular neoplasms mainly located in the posterior fossa of the central nervous system. Preoperative embolization of the feeding arteries is one proposal for reduction of intraoperative hemorrhage, although indications for the procedures should be evaluated carefully due to the potential complications. This retrospective study investigated clinical outcomes and complications of 15 patients with HBs in the posterior fossa to evaluate the safety and effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 25 publications
1
40
0
2
Order By: Relevance
“…Cornelius et al (3) reported their experience and concluded that particulate embolization is ineffective for treating cerebellar hemangioblastomas because of high risk of complications. Sakamoto et al (10) showed the mean volume of intraoperative blood loss in resection for hemangioblastomas was clearly less in the N-butyl cyanoacrylate group than in the Guglielmi detachable coils with or without polyvinyl alcohol group. Murai et al (8) also reported the effectiveness of preoperative embolization with N-butyl cyanoacrylate.…”
Section: Treatment Strategies For Cerebellar Hemangioblastomas: Simplmentioning
confidence: 99%
“…Cornelius et al (3) reported their experience and concluded that particulate embolization is ineffective for treating cerebellar hemangioblastomas because of high risk of complications. Sakamoto et al (10) showed the mean volume of intraoperative blood loss in resection for hemangioblastomas was clearly less in the N-butyl cyanoacrylate group than in the Guglielmi detachable coils with or without polyvinyl alcohol group. Murai et al (8) also reported the effectiveness of preoperative embolization with N-butyl cyanoacrylate.…”
Section: Treatment Strategies For Cerebellar Hemangioblastomas: Simplmentioning
confidence: 99%
“…With the application of microcatheter, microguidewire and other new materials as well as the development of high-resolution angiography and three-dimensional rotational revascularization techniques, preoperative embolization of CHB is becoming popular (Horvathy et al, 2011;Sakamoto et al, 2012). Currently, the most commonly used embolic materials for CHB embolization were physical embolic material (such as balloon and coils), PVA particles and liquid embolic agents (such as ONYX, NBCA).…”
Section: Discussionmentioning
confidence: 99%
“…Küçük partiküller daha distale giderek kapiller yatağı tıkar ve daha etkin embolizasyon sağlar. Ancak distale migrasyon, fizyolojik anastomozlar ile intrakraniyal dolaşıma geçme, kraniyal sinir paralizileri, akciğer embolileri gibi riskler için dikkatli olunmalıdır [6,7].…”
Section: A İntrakraniyal Tümörlerde Evtunclassified